2001
DOI: 10.1183/09031936.01.17303950
|View full text |Cite
|
Sign up to set email alerts
|

Allergic sensitization and diet: ecological analysis in selected European cities

Abstract: It has been postulated that the prevalence of atopic diseases and their increase over time are associated with regional differences in diet and trends. The results of an ecological correlation study comparing the mean daily intake of selected dietary constituents and the prevalence of allergic sensitization in adults in Europe is presented.Prevalence data from the European Community Respiratory Health Survey (ECRHS) were used. For eight out of 37 ECRHS centres (including 3,872 subjects), comparable dietary dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
37
1
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 33 publications
7
37
1
5
Order By: Relevance
“…Although the dietary pattern has not been evaluated in the present study, we observed a significantly low intake of riboflavin in a previous study on Vietnamese children (Quyen et al, 2004). A similar finding was reported by Heinrich et al (2001). In the European Community Respiratory Health Survey (ECRHS), they found a tendency towards decreasing allergic sensitization with higher riboflavin intake (OR ¼ 0.72, CI: 0.50-1.05; P ¼ 0.077) and vitamin A (OR ¼ 0.73, CI: 0.52-1.02; P ¼ 0.057), and a positive association with fruit intakes (OR ¼ 0.68, CI: 0.49-0.95; P ¼ 0.035).…”
Section: Discussionsupporting
confidence: 90%
“…Although the dietary pattern has not been evaluated in the present study, we observed a significantly low intake of riboflavin in a previous study on Vietnamese children (Quyen et al, 2004). A similar finding was reported by Heinrich et al (2001). In the European Community Respiratory Health Survey (ECRHS), they found a tendency towards decreasing allergic sensitization with higher riboflavin intake (OR ¼ 0.72, CI: 0.50-1.05; P ¼ 0.077) and vitamin A (OR ¼ 0.73, CI: 0.52-1.02; P ¼ 0.057), and a positive association with fruit intakes (OR ¼ 0.68, CI: 0.49-0.95; P ¼ 0.035).…”
Section: Discussionsupporting
confidence: 90%
“…Also, a recently published cross-sectional study reported a positive relationship between AA intake and allergic sensitisation among females (Trak-Fellermeier et al, 2004). Concerning monounsaturated fatty acids, Heinrich et al (2001) saw a positive association between monounsaturated fatty acid intake and the prevalence of allergic sensitisation in an ecological study among adults. Additionally, in a German subsample of the prospective EPIC cohort, a high intake of oleic acid was found to be positively associated with hay fever (Nagel et al, 2003).…”
Section: Discussionmentioning
confidence: 86%
“…It should be noted that, unlike that reported by Nagel and Linseisen, 2005, in the present work either oleic acid intake or margarine consumption was not associated with an increased risk of current asthma. Regarding MUFAs intake and asthma, Heinrich et al (2001) after adjusting for energy intake, observed the intake of MUFAs to be positively related to the prevalence of atopic disease. However, in a Taiwanese study involving 1166 adolescents, MUFA intake was found to be inversely proportional to asthma (OR ¼ 0.65 (0.43-0.99)) (Huang and Pan, 2001).…”
Section: Discussionmentioning
confidence: 99%